Prednisolone-loaded nanocapsules as ocular drug delivery system: development, in vitro drug release and eye toxicity. (September 2014) - Katzer, Tatiele; Chaves, Paula; Bernardi, Andressa; Pohlmann, Adriana; Guterres, Silvia S.; Ruver Beck, Ruy Carlos
Abstract Objective: To develop non-toxic aqueous ocular drug delivery systems containing prednisolone by means of its nanoencapsulation. Materials and methods: Nanocapsules were prepared by interfacial deposition of preformed polymer [poly(ε-caprolactone) or Eudragit® RS100]. Particle size distribution was determined by laser diffractometry, photon correlation spectroscopy and nanoparticle tracking analysis. Ocular irritation and cytotoxicity were evaluated in vitro on the chorioallantoic membrane (CAM) and rabbit corneal epithelial cell line, respectively. Results and discussion: Nanocapsules showed mean particle sizes between 100 and 300 nm and prednisolone encapsulation efficiency of around 50%. Controlled release of prednisolone occurred for 5 h for both formulations according to the biexponential model. Both formulations were found to be non-irritant in the CAM test and non-cytotoxic toward rabbit corneal epithelial cells. Conclusions: Encapsulation of prednisolone in nanocapsules was reported for the first time, being suitable for producing eye drops for the treatment of ocular inflammatory and no eye toxicity was indicated.